2011
DOI: 10.3758/s13421-011-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

Lack of color integration in visual short-term memory binding

Abstract: Bicolored objects are retained in visual short-term memory (VSTM) less efficiently than unicolored objects. This is unlike shape-color combinations, whose retention in VSTM does not differ from that observed for shapes only. It is debated whether this is due to a lack of color integration and whether this may reflect the function of separate memory mechanisms. Participants judged whether the colors of bicolored objects (each with an external and an internalcolor) were the same or different across two consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
3
18
0
1
Order By: Relevance
“…Several subsequent studies attempted and failed to replicate Luck and Vogel's finding regarding two‐colour objects (Delvenne & Bruyer, ; Olson & Jiang, ; Parra, Cubelli, & Della Sala, ; Wheeler & Treisman, ; Xu, 2002b). These studies generally found that combining two colours into a single object provided no benefit over remembering the same number of colours in separate objects, consistent with capacity limited by number of features, not objects.…”
Section: Objects and Featuresmentioning
confidence: 98%
“…Several subsequent studies attempted and failed to replicate Luck and Vogel's finding regarding two‐colour objects (Delvenne & Bruyer, ; Olson & Jiang, ; Parra, Cubelli, & Della Sala, ; Wheeler & Treisman, ; Xu, 2002b). These studies generally found that combining two colours into a single object provided no benefit over remembering the same number of colours in separate objects, consistent with capacity limited by number of features, not objects.…”
Section: Objects and Featuresmentioning
confidence: 98%
“…Therefore, a prioritization strategy at the object level will fail to help observers to become aware of relevant objects mismatching any spatial layout. On the other side of the spectrum lies the use of multiple search templates of each individual aspects of the Pepsi logo; a strategy that is too liberal and will prioritize many irrelevant objects in the fridge (e.g., a red Babybel cheese package will cause false alarms and will cause inefficient search (Luck & Vogel, 1997;Vogel et al, 2001; Luria & Vogel, 2011; c.f., Wheeler & Triesman, 2002;Olson & Jiang, 2002;Parra et al, 2011;Awh, Barton, & Vogel, 2007;Alvarez & Cavanagh, 2004). We can conclude from the current results that the interaction between VWM and visual awareness can be best described by a process that lies in between the two theoretical viewpoints: when two colors are to be encoded simultaneously, the colors are stored as conjunctions and not as independent features (Brady & Alvarez, 2011).…”
Section: Discussionsupporting
confidence: 49%
“…However, the debate whether VWM stores visual information as bound object representations or as independent features of objects is still ongoing since divergent evidence is reported by a number of subsequent studies: some studies replicate results which suggest bound object representations in VWM (Vogel, Woodman, & Luck, 2001;Luria & Vogel, 2010), whereas other studies report that memoranda are maintained as independent features (Delvenne & Bruyer, 2004;Olson & Jiang, 2002;Prra, Cubelli, & Della Sala, 2011;Wheeler & Triesman, 2002;Alvarez & Cavanagh, 2004). The multiple-resource theory assumes that there are separate pools of resources for holding features from different dimensions (Alvarez & Cavanagh, 2004;Delvenne & Bruyer, 2004;Olson & Jiang, 2002;Parra et al, 2011;Wheeler & Treisman, 2002). For example, Alvarez and Cavanagh (2004) reported that the object-based theory fails to entirely explain the VWM capacity.…”
Section: Vwm Content Regulates the Access To Visual Awareness But Atmentioning
confidence: 99%
“…The binding or conjunction of information in the shortterm memory allows a single multimodal representation to contain or to refer to representations present in different storage modalities. The binding of information of different modalities on the short-term memory is of fundamental importance for most cognitive functions such as associative memory (Craik 2006), planning and execution of sequences of movements (Annett 1995), face and name association (Godoy and Galera 2011), or shape and color association (Parra et al 2011). Despite its importance, little is known about the nature of the information integration process of different modalities in the short-term memory.…”
Section: Introductionmentioning
confidence: 99%